Pengunaan Openchart dalam Perancangan Sistem Promosi untuk UMKM : Solusi Digital untuk menjual Keripik Sanjai Secara Online - Ferdiansyah Bahri, Ferdi; Annas, Firdaus; Elin Yuspita, Yulifda; Arif, Mahmud; Alwi, Muhammad (JOVISHE : Journal of Visionary Sharia Economy, 2024)
The Sanjai Chips UMKM is a typical Minangkabau business engaged in food sales. Based on the results of an interview with the store owner, it was found that the owner still uses traditional methods of selling, which has led to the stagnation of the Sanjai Chips business. The promotion process for Sanjai Chips faces several challenges, particularly the lack of an online promotional platform. Additionally, the store's location is difficult for the general public to find. This is because the Sanjai Chips store does not have a website that can provide information about the products sold. To increase the sales of Sanjai Chips, a website is needed that can address these issues. In this digital era, we can take advantage of digital platforms that allow for broader sales reach, both locally and internationally. The goal of this article is to design a promotional system for the home industry of Sanjai Chips using the practical and effective OpenCart CMS. This study uses the PPE (planning, production, and evaluation) method. The research successfully designed an OpenCart-based promotional system to support the online marketing of Sanjai Chips, making it attractive, valid, practical, and effective. The designed system includes several main features such as a product catalog complete with images, descriptions, prices, and order management to facilitate customers in ordering the products they want. It is hoped that this research will result in a website that attracts customers from any region, enabling them to place orders without having to visit the store directly.